(untitled) (Research, Society and Development, 2022)
Considering that civil construction is one of the sectors that most impact the environment and that currently sustainability is one of the most commented subjects, this article aimed to perform a literature biblio review, analyzing the type of cement, trace, substitution content, tests performed and results obtained in mortars with incorporation of construction residues as a substitute for the aggregate and/or binder. The search for articles from journals, dissertations and theses occurred on the portal of the Coordination for the Improvement of Higher Education Personnel (CAPES), in the scielo database and in the academic Google. The period from 2009 to 2021 was considered for the analysis. After the research, the data were chosen from the reading of the title and abstract and when congruents underwent a critical analysis. Thus, 19 studies were selected that investigated the replacement of the aggregate with construction residues. Nine studies were selected in relation to the replacement of the paste by residues. The results of the tests of the selected studies were diversified, among the substitutions of the aggregate, it was observed that the traces 1:4, 1:4.5, 1:2:8 and 1:2:9 showed an increase in mechanical resistance. On the other hand, the mortars that tested the replacement of the paste by residues presented heterogeneous results for the physical parameters and tendency to reduce mechanical performance in hydraulic traits.